Successes and failures of attempts to embed socioeconomic dimensions in modeling for integrated natural resource management: Lessons from Thailand - B. Ekasingh (2018)
This paper discusses the necessity, successes and failures of attempts to embed socioeconomic aspects into integrated natural resource modeling. It uses experiences in Thailand over the last 20-30 years to illustrate advances and difficulties in this integration. The paper highlights strengths, weaknesses and the effectiveness of different approaches which are used to incorporate socioeconomic dynamic processes and impacts. Lessons learnt from Thai experiences starting from systems thinking and approaches through to attempts to model agricultural and watershed systems for management are reviewed. Historically successes in integrating socioeconomic dimensions with biophysical analyses lie most often in interaction with agricultural and natural resource economists who have more experience dealing with quantitative methods and "hard" numerical approaches than other social scientists. The need for the "soft" side of assessment is recognized but is not easily realized. Failures to include the perspectives of anthropologists, psychologists and sociologists in integrated assessments have been caused by departmental boundaries, inadequate linkages between social theories and differences in the agendas of these fields. Different approaches to the treatment of socioeconomic variables and processes are highlighted. Modeling approaches, such as agent-based systems or multi-agent systems are more tuned to socioeconomic concerns but must first pass the test of acceptability by policy makers who are used to top-down, simplified approaches to solving problems. Balancing, or even better, integrating "hard" and "soft" systems approaches will improve the relevance and validity of the models to solve agricultural/natural resource problems.